PERUSAHAAN PEMBIAYAAN SYARIAH DI INDONESIA (SEBUAH TINJAUAN ANALISIS TERHADAP PERUSAHAAN PEMBIAYAAN PT. FIF SYARIAH) - muhaimin, muhaimin (At-Taradhi Jurnal Studi Ekonomi, 2012)
FIF Syariah is a non-bank Sharia-based unit running a financing business. The fact thatit follows Sharia precepts and that the majority of Indonesian citizens are Muslims make it pro-spective to be an alternative in distributing funds to people in Indonesia. In middle term, there isa big chance that FIF Syariah will have a speedy growth since the number of company that openSharia financing units is still relatively small. It is important that every stakeholder pay attentionsto these Sharia financing units so they can grow and stay in the right track (complying withIslamic law). The commitment of the government will certainly support the development ofSharia financing in Indonesia.